2023
DOI: 10.1097/hjh.0000000000003558
|View full text |Cite
|
Sign up to set email alerts
|

A randomized, placebo-controlled, trial to assess the photosensitizing, phototoxic and carcinogenic potential of hydrochlorothiazide in healthy volunteers

Felix Götzinger,
Mathias Hohl,
Lucas Lauder
et al.

Abstract: Background and aims: Pharmacovigilance reports, associating hydrochlorothiazide (HCT) with skin cancer, resulted in a significant decrease of HCT prescriptions for hypertension and heart failure. Whether HCT exhibits phototoxic properties thereby causing skin cancer remains unknown. This study aimed to examine the photosensitizing, phototoxic and carcinogenic potential of HCT in a randomized, placebo-controlled, double-blind trial in vivo and also in vitro. Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 46 publications
(65 reference statements)
0
1
0
1
Order By: Relevance
“… 26 Another recently published, small, randomized, placebo-controlled trial concluded that HCTZ did not increase photosensitivity and was not associated with phototoxic or carcinogenic reactions. 27 More research is needed given the heterogeneous conclusions of previous studies.…”
Section: Discussionmentioning
confidence: 99%
“… 26 Another recently published, small, randomized, placebo-controlled trial concluded that HCTZ did not increase photosensitivity and was not associated with phototoxic or carcinogenic reactions. 27 More research is needed given the heterogeneous conclusions of previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…27 UVA-Strahlung dringt bis in die Dermis vor und interagiert dort mit Fibroblasten. 45 46 Darüber hinaus bestätigt die vorliegende Studie die epidemiologischen Daten für AFX/PDS mit einer starken männlichen Dominanz (88,9% Männer) und überwiegend betroffenen älteren Patienten, wobei 84,5% der AFX/PDS-Diagnosen bei Patienten über 75 Jahren gestellt wurden (Tabelle 1). 6,11 Zusätzlich stehen die vorliegenden Daten im Einklang mit früheren Erkenntnissen, dass die Diagnose eines AFX/PDS mit weiteren NMSC assoziiert ist, da 54,1% der AFX/PDS-Patienten mindestens ein weiteres vorbekanntes NMSC aufwiesen.…”
Section: Diskussionunclassified
“…In this issue of the Journal, an experimental study of the phototoxic and carcinogenic potential of HCT is reported [9]. The authors studied 30 healthy individuals.…”
mentioning
confidence: 99%